(untitled) - United Nations Industrial Development Organization (UNIDO) (Ha Noi, 2011)
The report presented recommendations for the Vietnamese Government, including reformulation of industrial strategies and policies, industrial diversification into high value-added products, human resources development for manufacturing, technology development and targeting quality FDI for manufacturing.
Keywords: Competition,Cạnh tranh,Economic development,Phát triển kinh tế; Vietnam,Việt Nam,Vietnam,Việt Nam